Analgesic activity of Eugenia jambolana leave constituent: A dikaempferol rhamnopyranoside from ethyl acetate soluble fraction. (August 2014) - Lingaraju, Madhu Cholenahalli; Anand, Shikha; Balaganur, Venkanna; Kumari, Rashmi Rekha; More, Amar Sunil; Kumar, Dinesh; Bhadoria, Brijesh Kumar; Tandan, Surendra Kumar
Abstract Context: Eugenia jambolana Lam. (Myrtaceae) is a medicinal plant used in folk medicine for the treatment of diabetes, inflammation, and pain. Objective: We investigated the antinociceptive effect of kaempferol-7-O-α-l-rhamnopyranoside]- 4′-O-4′-[kaempferol-7-O-α-l-rhamnopyranoside (EJ-01), isolated from the E. jambolana leaves. Materials and methods: EJ-01 (3, 10, and 30 mg kg−1, orally) was assessed for peripheral (formalin-nociception and acetic acid-writhing) and central (hot plate and tail flick test) analgesic activity in mice and the in vitro anti-inflammatory activity (25, 50, and 100 µg mL−1) in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. Results and discussion: EJ-01 (10 and 30 mg kg−1) significantly inhibited mean writhing counts (37.74 and 36.83) in acetic acid writhing and paw licking time (55.16 and 45.66 s) in the late phase of the formalin test as compared with the respective control (60.66 and 104.33 s). EJ-01 did not show analgesic activity in central pain models. Significant reduction in the tumor necrosis factor (TNF)-α (295.48, 51.20, and 49.47 pg mL−1) and interleukin (IL)-1β (59.38, 20.08, and 15.46 pg mL−1) levels were observed in EJ-01-treated medium (25, 50, and 100 µg mL−1) as compared with vehicle-treated control values (788.67 and 161.77 pg mL−1), respectively. Significant reduction in total nitrite plus nitrate (NOx) levels (70.80 nmol) was observed in the EJ-01-treated medium (100 µg mL−1) as compared with the vehicle-treated value (110.41 nmol). Conclusion: EJ-01 is a valuable analgesic constituent of E. jambolana leaves and this study supports the pharmacological basis for the use of this plant in traditional medicine for curing inflammatory pain.